X inactivation patterns in females with Alport's syndrome: a means of selecting against a deleterious gene?. Issue 9 (September 1992) - Vetrie, D; Flinter, F; Bobrow, M; Harris, A
Abstract : The patterns of X chromosome inactivation in 43 females from families segregating classic Alport's syndrome (AS) (X linked hereditary nephritis with deafness) have been analysed. AS carrier females have a most variable clinical course. The aim of the study was to establish whether there was any correlation between the X inactivation pattern of a carrier female and the severity of her disease. No correlation was found in DNA derived from peripheral blood lymphocytes. However, it remains possible that differential patterns of X inactivation may occur in the tissues affected by AS, namely the basement membrane of the kidney, eye, and ear.